Assessment of NUDT5 in Endometrial Carcinoma: Functional Insights, Prognostic and Therapeutic Implications - Hongfei Yu; Lingling Zu; Yuqin Zang; Fei Teng; Tao Wang; Ming Wu; Yingmei Wang; Fengxia Xue (Biomedicines)
Background: Endometrial carcinoma (EC) is the most common gynecological malignancy, with increasing incidence contributing to a significant global health burden. Despite recent advancements, the molecular mechanisms underlying EC progression remain insufficiently understood, limiting the development of targeted therapies. This study aims to investigate the role of nucleoside diphosphate-linked moiety X motif 5 (NUDT5) in EC and evaluate its potential as a biomarker and therapeutic target. Methods: This study analyzed gene expression data from The Cancer Genome Atlas and performed tissue microarray validation to assess NUDT5 expression in EC samples. Immunohistochemistry was used to evaluate NUDT5 protein levels and their correlation with clinicopathological features. Functional assays, including cell proliferation, migration, invasion, and apoptosis analysis, were conducted to determine the oncogenic effects of NUDT5 in vitro. Weighted gene co-expression network analysis (WGCNA) and experimental validation were performed to explore the impact of NUDT5 on the PI3K-AKT signaling pathway, while tumor growth assays in xenograft models assessed the therapeutic potential of NUDT5 inhibition in vivo. Results: NUDT5 was significantly overexpressed in EC tissues and correlated with advanced histological grade and poor prognosis. Functional experiments demonstrated that NUDT5 promotes cell proliferation, migration, and invasion while inhibiting apoptosis. Mechanistically, NUDT5 activated the PI3K-AKT pathway, contributing to tumor progression. In vivo, NUDT5 knockdown suppressed tumor growth. Conclusions: These findings suggest that NUDT5 functions as an oncogene in EC, serving as a potential diagnostic and prognostic biomarker. Targeting NUDT5 may provide a novel therapeutic strategy for EC management.